SEJARAH HABAIB DI INDONESIA - Hasna Nadiya; Nadiya Nor Oktari; Muh. Dimas Affandi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research aims to know and analyze in depth the important role of Habaib in the process of spreading Islam in Indonesia since their arrival in the 13th century from Hadramaut, Yemen. The focus of this research is more focused on (1) knowing the history of Habaib in Indonesia, (2) knowing the dedication of Habaib to contribute in order to introduce the community to the pattern of religious life, (3) knowing the views, attitudes and tendencies of the Indonesian people towards Habaib significantly in the aspects of education, strengthening moral values, and developing social solidarity in Indonesian society. This research uses a qualitative method, in which data is obtained from various sources, such as books, journals, and other written sources. These data are used to enrich the material content and discussion of the research. This qualitative research focuses on investigation and understanding to explore the historical journey of the Habaib and their impact on culture in Indonesia, as well as the importance of preserving their legacy in contemporary society. The results show that the influence of the Habaib during their time contributing to the Indonesian movement in building moral values, cultural acculturation, and national struggle as well as enriching spiritual practices with the teachings of Ahlussunnah wal Jama'ah and Sufism, in shaping national identity and the foundations of post-independence democracy, and calls for further research into the role of the Habaib.